Problems Encountered with Online Class Participation - Arzagon, Rosmalin G.; Zaragoza, Melody A.; Mecida, Sherry V. (ASEAN Journal of Educational Research and Technology, 2022)
The primary objective of this descriptive study was to find out the problems with online class participation among college students during the academic year, 2020-2021, the onset of the COVID -19 pandemic. It was conducted at Notre Dame of Tacurong College, City of Sultan Kudarat. The respondents of the study were 392 students across courses and year levels representing 77.17% of 508 students who constituted the total number of students who answered the questionnaire. Findings showed that the mean ratings of the seven items range from 2.23 to 2.72 and each was described by the respondents as a Moderate Problem encountered with online class participation. However, Item 2, Finding a quiet place where you could do your class works online, obtained the highest mean of 2.72 (SD = 0.92) and was described as a Moderate Problem. Item 7, Fitting the course with your work schedule, if you work for pay, got the lowest mean rating of 2.23 (SD = 0.98) and was described also as a Moderate Problem to the students.